2016
DOI: 10.1159/000442894
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Laser Doppler Measurements of Microcirculation in the Deep Brain Structures: A Method for Potential Vessel Tracking

Abstract: Background: Laser Doppler flowmetry (LDF) can be used to measure cerebral microcirculation in relation to stereotactic deep brain stimulation (DBS) implantations. Objective: To investigate the microcirculation and total light intensity (TLI) corresponding to tissue grayness in DBS target regions with high-resolution LDF recordings, and to define a resolution which enables detection of small vessels. Methods: Stereotactic LDF measurements were made prior to DBS implantation with 0.5-mm steps in the vicinity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…The blood perfusion did not show any significant difference (p > 0.05) in the tumor that could indicate a considerably higher perfusion in the tumor. It is previously investigated that blood flow measured with LDF is directly related with the vessel size, type and orientation [30,38] and the 0.5 mm insertion step is assumed to suffice for the look-ahead distance of the forward-looking probe [27,39]. Other methods of vessel detection are based on re-emission spectroscopy [19] which is an easy to implement module but might not be able to distinguish vessels (blood flow) from minor bleeding during the in vivo measurements.…”
Section: Microvascular Blood Flow and Vessel Trackingmentioning
confidence: 99%
See 2 more Smart Citations
“…The blood perfusion did not show any significant difference (p > 0.05) in the tumor that could indicate a considerably higher perfusion in the tumor. It is previously investigated that blood flow measured with LDF is directly related with the vessel size, type and orientation [30,38] and the 0.5 mm insertion step is assumed to suffice for the look-ahead distance of the forward-looking probe [27,39]. Other methods of vessel detection are based on re-emission spectroscopy [19] which is an easy to implement module but might not be able to distinguish vessels (blood flow) from minor bleeding during the in vivo measurements.…”
Section: Microvascular Blood Flow and Vessel Trackingmentioning
confidence: 99%
“…Measurement at each position took around 20 s and thus the added time to the routine procedure was around 15 min. The step size of the mechanical device can be decreased to 0.5 mm [27], however, this will also increase the measurement time for a 50 mm long trajectory. In the routine application, a much quicker procedure is desired where the probe can be proceeded continuously.…”
Section: Intraoperative Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within a few seconds from the movement, the laser Doppler signal is stable and the captured signals allow calculation of, for instance, mean perfusion, heart rate and peakto-peak of the microcirculation as well as the TLI at a specific position in the brain tissue. The microcirculation signal can also be used to track larger vessels along the trajectory, (46) and the TLI signals have been used to determine "bar-codes" towards two of the most common DBS targets; the STN and the Vim. (44) Figure 6 shows perfusion and TLI signals post-processed to "bar-codes" following insertion with the mechanical device at 1 mm steps towards the STN.…”
Section: Ldf As Navigational Tool During Stereotactic Neurosurgerymentioning
confidence: 99%
“…A recent study on patients implanted with DBS electrodes using optical guidance has shown that both TLI, i.e., grey-white tissue differences, and microvascular changes can be recorded with 0.5 mm resolution, and thus local blood flow and TLI peaks can be identified with this resolution. (46) An optical resolution of about 0.5-1 mm can therefore be considered reasonable in stereotactic and functional neurosurgery, especially as the DBS leads and RF electrodes are about 1.3 mm and 1.5-2 mm in diameter, respectively. These diameters are, on the other hand, rather large compared to the nuclei, which measure a few millimeters up to about 1 cm.…”
Section: Measurement Depth and Resolutionmentioning
confidence: 99%